(untitled) (Global Journals of Research in Engineering, 2013)
This paper focus on a finger typed electrode based electro-optical photo mixing demodulator. This device is fabricated on high resistivity silicon in custom technology. The main performance indicatorssuch as DC characteristics, DC and AC demodulation contrast and phase-linearity measurement of a test sample are experimentally characterized. Experimental results exhibit a good DC charge separation and good dynamic demodulation capabilities from 100Hz to 30MHz.The average linearity error of finger typed electrode device for square wave 4.09% has been measured. The dependency of the device performance on modulation frequency and voltage is also discussed.